The effects of classic altitude training on hemoglobin mass in swimmers - Wachsmuth, Nadine; Völzke, C.; Prommer, N.; Schmidt-Trucksäss, A.; Frese, Falko; Spahl, O.; Eastwood, A.; Stray-Gundersen, J.; Schmidt, W. (European journal of applied physiology, 2013)
Aim of the study was to determine the influence of classic altitude training on hemoglobin mass (Hb-mass) in elite swimmers under the following aspects: (1) normal oscillation of Hb-mass at sea level; (2) time course of adaptation and de-adaptation; (3) sex influences; (4) influences of illness and injury; (5) interaction of Hb-mass and competition performance. Hb-mass of 45 top swimmers (male 24; female 21) was repeatedly measured (~6 times) over the course of 2 years using the optimized CO-rebreathing method. Twenty-five athletes trained between one and three times for 3-4 weeks at altitude training camps (ATCs) at 2,320 m (3 ATCs) and 1,360 m (1 ATC). Performance was determined by analyzing 726 competitions according to the German point system. The variation of Hb-mass without hypoxic influence was 3.0 % (m) and 2.7 % (f). At altitude, Hb-mass increased by 7.2 ± 3.3 % (p < 0.001; 2,320 m) and by 3.8 ± 3.4 % (p < 0.05; 1,360 m). The response at 2,320 m was not sex-related, and no increase was found in ill and injured athletes (n = 8). Hb-mass was found increased on day 13 and was still elevated 24 days after return (4.0 ± 2.7 %, p < 0.05). Hb-mass had only a small positive effect on swimming performance; an increase in performance was only observed 25-35 days after return from altitude. In conclusion, the altitude (2,320 m) effect on Hb-mass is still present 3 weeks after return, it decisively depends on the health status, but is not influenced by sex. In healthy subjects it exceeds by far the oscillation occurring at sea level. After return from altitude performance increases after a delay of 3 weeks.